2019
DOI: 10.1038/s41372-019-0335-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of early postnatal prediction models for survival in congenital diaphragmatic hernia

Abstract: Objective To compare the PF-PCO 2 equation-partial pressure of arterial oxygen (PaO 2)/fraction of inspired oxygen (FiO 2) minus partial pressure of carbon dioxide (PCO 2)-to three other tools for postnatal prediction of survival in infants with congenital diaphragmatic hernia (CDH). Study design A retrospective analysis of 203 infants with CDH from 1 January 2003 to 30 June 2018. Area under the curve (AUC) analysis was performed for survival and secondary outcomes of survival without extracorporeal membrane o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(53 reference statements)
2
7
0
Order By: Relevance
“…Previous studies have reported that the predictor's of poor outcome included lung to head ratio <1.4, significantly elevated PCO2 (>90) in the first 24 hours, severe PPHN with cardiac dysfunction, hypoplastic left ventricle and liver and stomach herniation to thorax and prematurity. [5,6,[9][10][11][12] Our data concur with these markers but liver and stomach herniation were not poor outcome predictors.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous studies have reported that the predictor's of poor outcome included lung to head ratio <1.4, significantly elevated PCO2 (>90) in the first 24 hours, severe PPHN with cardiac dysfunction, hypoplastic left ventricle and liver and stomach herniation to thorax and prematurity. [5,6,[9][10][11][12] Our data concur with these markers but liver and stomach herniation were not poor outcome predictors.…”
Section: Discussionsupporting
confidence: 84%
“…[2] Several variable predictors of poor outcome have been identified in various studies. [3][4][5][6][7][8][9] In this single center study, we have reviewed the outcome of newborns with CDH and attempted to identify predictors of outcome in our cohort.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that the CDHSG model can predict survival with an AUC of 0.79 9 . In some studies, it has been revealed that the AUC value of the CDHSG model is 0.74, providing a good survival prediction, and the mortality rate increases as the risk score increases 7,13 . In their study, Patel et al 8 reported a high performance with AUC 0.88 in the prediction of PCO 2 > 60 mortality in the first 24 h of blood gas.…”
Section: Discussionmentioning
confidence: 88%
“…It has been revealed that in low birth weight or preterm infants, CDH progresses poorly, and the survival rate is low 2,4–6 . The degree of pulmonary hypoplasia, the adequacy of ventilation oxygenation and pulmonary hypertension determines the course of CDH 1,2,7 . In 2014, a clinical prediction rule consisting of birth weight, 5‐min Apgar score, pulmonary hypertension, accompanying chromosomal anomaly, or congenital cardiac anomalies was developed by the Congenital Diaphragmatic Hernia Study Group (CDHSG) to determine the severity of CDH 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation